Al-Tasawuf wa Azmah al-MustadÄmah: MuqÄrabah Mutaâ€™addidah al-Takhaá¹£á¹£uá¹£Ät Li IdÄrah al-NufÄyÄt fÄ« Indonesia Mustawá¸¥Ät min MafhÅ«m al-KhilÄfah fÄ« RasÄil al-NÅ«r: Tasawwuf and Sustainability Crisis: A Multidisciplinary Approach to Waste Management in Indonesia Inspired by the Concept of Caliphate in the Risale-i Nur - Mudin, Moh. Isom; Huringiin, Nabila; Ouannes, Mohamed Hedi; TÃ¼rkoÄŸlu, TuÄŸba (Tasfiyah: Jurnal Pemikiran Islam, 2024)
This research explores the relationship between the concept of Khilafah in the Risale-i Nur and the "Zero Waste" movement in Indonesia. The study utilizes a literature review, including a compilation of Risale-I Nur, data from the Zero Waste program in Indonesia's National Waste Management Information System (SIPSN), and related literature. This data is then qualitatively analyzed and subjected to content analysis to describe the relevance and implications of it concept on the Indonesia Zero Waste movement. Â The research demonstrates that the concept of Khilafah transcends the anthropocentric and ecocentric perspectives, emphasizing human responsibility towards the environment. The research further illustrates how the concept of Khilafah utilizes the "Law of Purification" as a foundation for the "Zero Waste" concept. Despite the progress made by Indonesia in waste management, significant challenges remain. The research highlights the role of the Khilafah concept in fostering religious awareness and sensitivity within the "Zero Waste" movements. It elucidates that the connection between the Nursian Khilafah and the "Zero Waste" movements constitutes a religious basis and sensitivity that requires continuous attention. The research is expected to provide profound insights into the potential of the Nursian Khilafah in addressing waste problems and supporting the "Zero Waste" movement in Indonesia